MANAJEMEN KURIKULUM ADAPTIF DALAM MENINGKATKAN EFEKTIFITAS PEMBELAJARAN - Shokhif Mas'ud Wahyudi (MANAGERE : Indonesian Journal of Educational Management, 2021)
Learning in emergency conditions cannot be carried out as usual, however, students still get education and learning services, namely through distance learning by carrying out learning activities from home. The purpose of this paper is to describe the governance of the adaptive curriculum model of the education unit in improving effective learning adapted to the conditions and needs of the school/madrasah. The method used is a qualitative method with a library research approach. The results of the adaptive curriculum development model are divided into three, namely: 1) General curriculum model (regular). 2) General curriculum model with modifications. 3) Individualized curriculum model Effective learning if teaching activities can achieve the objectives according to the initial planning. Learning is said to be effective when students can absorb the subject matter and efficiently. Emergency learning models include: Project Based Learning, online Method, Offline Method, Home Visit Method, Integrated Curriculum, Blended Learning.